2010
DOI: 10.2174/1874120701004020003
|View full text |Cite
|
Sign up to set email alerts
|

Considerations for Thermal Injury Analysis for RF Ablation Devices~!2009-09-09~!2009-12-19~!2010-02-04~!

Abstract: Background:The estimation of lesion size is an integral part of treatment planning for the clinical applications of radiofrequency ablation. However, to date, studies have not directly evaluated the impact of different computational estimation techniques for predicting lesion size. In this study, we focus on three common methods used for predicting tissue injury: (1) iso-temperature contours, (2) Cumulative equivalent minutes, (3) Arrhenius based thermal injury.Methods:We created a geometric model of a multi-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…In the past study, it was suggested that if damage function exceeds the value of 0.53, then first-degree burns are imminent [43]. Further, the necrosed tissues lead to the transient cessation of localized blood flow [44]. Therefore, the proposed CEM43°C-based Arrhenius model could be used to predict the thermal injury during bone grinding.…”
Section: Tissue Damagementioning
confidence: 99%
“…In the past study, it was suggested that if damage function exceeds the value of 0.53, then first-degree burns are imminent [43]. Further, the necrosed tissues lead to the transient cessation of localized blood flow [44]. Therefore, the proposed CEM43°C-based Arrhenius model could be used to predict the thermal injury during bone grinding.…”
Section: Tissue Damagementioning
confidence: 99%
“…where ρ b is density of blood, c b specific heat of blood, T b blood temperature (37°C), ω b blood perfusion coefficient (ω b = 0.0155 s -1 ), 8 and β is a coefficient which took the values of 0 and 1, according to the value of the thermal damage: β = 0 for Ω ≥ 4.6 and β = 1 for Ω < 4.6. The parameter Ω is assessed by the Arrhenius damage model, 9 which associates temperature with exposure time using a first-order kinetics relationship:…”
Section: Governing Equations and Model Characteristicsmentioning
confidence: 99%
“…where R is the universal gas constant, A (7.39 × 10 39 s −1 ) is a frequency factor and ΔE (2.577 × 10 5 J/mol) is the activation energy for the irreversible damage reaction. 9,10 We assessed the thermal damage by the D99 isoline, 11 which corresponds to Ω = 4.6 (99% probability of cell death). The location of the D99 isoline defined the size of the coagulation zone.…”
Section: Governing Equations and Model Characteristicsmentioning
confidence: 99%
“…Mathematical modeling has been an efficient and low cost modality in both design and treatment planning [ 22 ]. Models have been developed to simulate the temperature distributions of tissue during the treatment [ 4 , 23 - 26 ]. The complexity of the tumor composition, the influence of heterogeneous electrical conductivity, thermal conductivity, blood perfusion rate, and the specific distribution of blood vessels on the results have been studied [ 27 - 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…The RF frequency used is 460 kHz. As the wavelength of the electromagnetic field is much longer than the electrode, the quasi-static approximation of the electrical field in the tissue is applied [ 26 , 42 ],…”
Section: Introductionmentioning
confidence: 99%